The survival of peri-urban agrarian livelihoods in transitioning spaces of KwaZulu- Natal, South Africa - de Silva, Umesha (University of Ottawa (Canada), 2011)
South Africa's unique history of racial segregation and spatial dynamics severely undermined the role and tradition of small-scale agriculture among the black population. In order to redress past injustices, the post-apartheid government aims to re-invigorate agriculture to improve food security and economic growth, with a particular focus on establishing a class of black small-scale farmers. However, changing livelihood trajectories, threats to sustainable agriculture, and the diverse and complex rural-urban interface challenge the sustainable role that small-scale farming can assume in peri-urban areas. On these premises, the study offers a critical reflection of the future of small-scale farming in one peri-urban community located in one of South Africa's former homelands -- KwaZulu-Natal (KZN). The overarching objectives of this thesis are: 1) to draw upon the Sustainable Livelihoods Framework to gather data in order to explore livelihood strategies of small-scale, peri-urban farmers in Umzinyathi, KZN; 2) to analyze the effects of rural-urban transitions on small-scale farmers in Umzinyathi, KZN using a political ecology framework, with an emphasis on marginalization and degradation; and 3) to reflect upon the current policy framework that has been drafted for small-scale farming in South Africa. Qualitative and quantitative methods were used for data collection and analysis. Participatory research methods included: (a) the collection of semi-structured interviews and surveys from forty small-scale farmers, focusing on the respondent's livelihood; and (b) semi-structured, key informant interviews with two academics, three development practitioners, a tribal chief, and two commercial farmers. The fieldwork was conducted over three months between October and December 2010. The results of the survey suggested the following trends: tribal authorities play a large role in allocating land to resource-poor households, but land tenure is weak, and access to land is still limited to some; livelihood diversification is low and households assume their income primarily from social assistance and farming activities; farmers' access to markets is restricted due to infrastructural and production barriers; and the climate conditions are perceived to have changed the nature of farming, but adaption strategies to climate shocks and stresses are limited. Through comparing field data with the literature on agriculture and livelihoods in South Africa, the study identified several trends, which could either foster agricultural livelihoods in peri-urban areas, and which could not. It was found that rural to urban transitions could explain themes of marginalization and degradation in the research site related to the degradation of the natural resource base, the disintegration and marginalization of tribal authorities, and the marginalization of livelihoods through diminishing numbers of economic opportunities. This in turn had tremendous impacts on the feasibility of small-scale farming to improve food security, peri-urban livelihoods, and inspire economic development. The study believes that South Africa's current policy framework for small-scale farming can make vital contributions to both the farm and non-farm sectors of the peri-urban economy, but that its uptake can improve with additional communication, monitoring, and training. To this extent, the study suggests the implementation of farming associations to act as intermediary bodies between the state, agricultural cooperatives and individual farmers. The study also suggests areas in the peri-urban non-farm sector that could thrive in an agriculturally-driven economy.
Keywords: Political Science, International Relations.